2006
DOI: 10.1080/02699050500487910
|View full text |Cite
|
Sign up to set email alerts
|

Tracking neuropsychological recovery following concussion in sport

Abstract: This study illustrates the importance of analysing individual athletes' test data because group analyses can obscure slow recovery in a substantial minority of athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(197 citation statements)
references
References 47 publications
10
185
1
1
Order By: Relevance
“…Previous studies have demonstrated that athletes tend to recover from perceived symptoms and their neurocognitive performance normalizes within 3-10 days, with a smaller percentage of individuals that require more time to recover. 1,12,[14][15][16]18 Previous studies have also demonstrated that players who sustained a concussion in a season were 3 times more likely to sustain a second concussion in the same season compared with uninjured players. 11,29 Five (29%) of 17 players who sustained a concussion in this study also sustained a second concussion in the same season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that athletes tend to recover from perceived symptoms and their neurocognitive performance normalizes within 3-10 days, with a smaller percentage of individuals that require more time to recover. 1,12,[14][15][16]18 Previous studies have also demonstrated that players who sustained a concussion in a season were 3 times more likely to sustain a second concussion in the same season compared with uninjured players. 11,29 Five (29%) of 17 players who sustained a concussion in this study also sustained a second concussion in the same season.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published return-to-play concussion-focused studies have been difficult to compare, as they have been based on different surveillance and return-to-play protocols. 1,10,12,[14][15][16]18,24,28 The primary goal of the present study was to prospectively measure the duration of medical restriction from play (return-to-play period) after each physicianobserved and -diagnosed concussion or recurrent concussion, by direct clinical evaluation augmented with the SCAT2 and ImPACT neuropsychological tools. We studied players from 2 teams of junior ice hockey players during a single regular (36-game) season using the Zurich return-to-play protocol.…”
mentioning
confidence: 99%
“…Plainly, presence of litigation is a major confound in research in mTBI and its presence in research studies has likely obscured the true effects of concussion, including PPCS. Also, whenever analyzing group data, if all subjects with concussion are examined at a particular time period, the effects on individual subjects who may be symptomatic get washed out by the total group effects (Iverson et al, 2006a;Kent, 2007;McHugh et al, 2006;Sterr et al, 2006). This is a very important point, because few studies compare symptomatic versus non-symptomatic subjects who have been concussed and those who do, find those who are symptomatic to have greater neuropsychological impairment (Collie et al, 2006;Iverson et al, 2004;Sterr et al, 2006).…”
Section: Limitations Of Neuropsychological Research To Advance the Fimentioning
confidence: 99%
“…The utility, reliability, and validity of ImPACT have been discussed in the literature. 5,17,[25][26][27] For the final sample in this study, data extracted from each de-identified baseline testing record included the following demographics: date of birth, testing date, sex, current sport, and number of prior concussions. Neurocognitive data extracted verbal memory, visual memory, visual motor (processing) speed, reaction time, impulse control composite scores, total symptom score, and the validity of the baseline test.…”
Section: Materials and Proceduresmentioning
confidence: 99%